Digital Transformation in the Manufacturing Industry in India to Optimise the Efficiency of Productivity - Boobalan, Sureshkumar (Digital Repository of Theses, 2025)
The digital world has metamorphosed how products are being introduced in the market. Digital efficiency promises to boost overall productivity, with its precise formulations and focused execution. Changes are inevitable, and owing to this evolution, coupled with the massive impact of the Fourth Industrial Revolution (Industry 4.0) that promotes digitisation, developing countries like India are slowly embracing this formula. Like most developing countries, the manufacturing industry in India has encountered some hurdles and obstructions while adapting to digital methods in its everyday operations. This study aims to provide a practical solution to manufacturing businesses in adapting to digital transformation by providing agile templates and resources for seamless execution. Thanks to the gradual increase in literacy and a technically sound younger generation, businesses are all the more required to digitally transform their operations, to not just meet users' expectations, but also create a high market share, in an already highly competitive sector. Some of the key reasons that are a challenge for most manufacturing businesses in India, especially when it comes to embracing digital transformation, include factors such as cultural, political, economic and social influence. There is a lack of a defined SOP on how to implement digital transformation. This study proposes an AIM (Agile Implementation Model) framework that addresses various challenges encountered by businesses while adapting to digital transformation strategies. The AIM framework is a structured approach to implementing, testing and training digital practices in every stage of the organisation's growth trajectory, starting from the most critical tasks. It helps by adding the current procedures (status quo) to a framework that will identify the crucial points to implement at the beginning of creating a brand new process. The framework breaks down the complexity of digital transformation by creating stages in each process, comprising all the critical components such as stakeholders, team formation and a defined objective. It explains the creation of these ‘X’ stages, right from the start to implementation, testing and problem solving. Due to this, the process becomes data-driven and not assumption-based. As a best practice, the AIM is best suited to be implemented in a limited fashion at the start, thereby focusing on critical issues before scaling it to an organisational level. The framework also provides templates that help stakeholders identify critical issues. One of the key reasons why the framework classifies the processes into different unique stages is to keep it non-biased and easy for stakeholders to execute. Needless to say, these stages are formulated basis testimonials of industry experts who have shared a high need for a defined methodology to incorporate digital transformation strategies in their businesses. The implementation, thus, takes into account every stage of the process, one at a time.